Efficacy of a school-based education intervention on the consumption of fruits, vegetables and carbonated soft drinks among adolescents - Kazi R Ahmed; Tracy Kolbe-Alexander; Asaduzzaman Khan (Cambridge University Press, 2023)
Abstract Objectives: To evaluate the efficacy of a school-based education intervention on the consumption of fruit, vegetables and carbonated soft drinks among adolescents. Design: Cluster-randomised controlled trial. Setting: Eight secondary schools from Dhaka, Bangladesh, participated in this trial and were randomly allocated to intervention (n 160) and control groups (n 160). Participants: A total of 320 students from 8th to 9th grades participated and completed the self-reported questionnaires at baseline, and at 8 and 12 weeks. The intervention included weekly classroom-based nutrition education sessions for students and healthy eating materials for students and parents. Repeated measures ANCOVA was used to assess the effects of the intervention. Results: Daily fresh fruit intake was more frequent in the intervention (26 %) compared to the control group (3 %) at 12 weeks (p = 0·006). Participants from the intervention group also reported a significantly (P < 0·001) higher (49 %) proportion of fresh vegetable intake compared to the control group (2 %) at 12 weeks. Frequency of daily carbonated soft drinks intake decreased (25 %) in the intervention group at 12 weeks compared to baseline, while it remained unchanged in the control group; the interaction effect was observed significant (P = 0·002). Conclusion: Our school-based education intervention increased the daily frequency of fresh vegetables and fruit intake and decreased carbonated soft drink consumption among adolescents in the intervention group. There is a need for scaling up the intervention to engage students and empower them to develop healthy dietary habits.